Examining the risk factors and needs of veterans involuntarily doubling-up with family or friends. Issue 3 (2nd September 2019) - Cusack, Meagan; Montgomery, Ann Elizabeth
ABSTRACT: Prior research has found that individuals who are involuntarily doubling-up are at greater risk of experiencing homelessness and continued housing instability. Using intake assessment data from community organizations that provide homelessness prevention services to Veterans, this study examines the risk factors and needs of those living in the home of another involuntarily on a temporary basis to inform programs aimed at addressing barriers to stable independent housing. Those with a poor housing history, physical disability, chronic health condition, mental health issue, or substance abuse problem have greater odds of living in the home of another involuntarily. The needs of those involuntarily doubling-up could be addressed through increased connections to healthcare, housing assistance, child care, and basic necessities.